Strategi Public Relations Radio Geronimo Yogyakarta dalam Mempertahankan Citra Perusahaan - Arlin Latifa; Benni Setiawan (MediaTor (Jurnal Komunikasi), 2019)
This research focused on the production and broadcasting on radio programs. In this study, researchers will dig deeper into Geronimo’s radio of Yogyakarta public relations strategy in maintaining the company’s image. This research is a qualitative descriptive study using purposive sampling technique because researchers want to examine more deeply about Public Relations (PR) strategies by taking samples from data sources. Data collection is done by interviews, observation and documentation. Data checking is done by source triangulation. Data analysis was carried out by interactive analysis of Miles and Huberman, through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study showed public relations has carried out the function of maintaining the image by working on specific market segmentation, namely groups of youth (students). Student segmentation is the right target market considering that Yogyakarta is known as a student city. The implication of this research is that public relations needs to continue to make smart innovations to maintain the target market, so that the company’s image is getting stronger (have a good character).